Intermediaries in the Online Advertising Market - Anna D'Annunzio; Antonio Russo (Center for Economic Studies and ifo Institute (CESifo), 2021)
A large share of the ads displayed by digital publishers (e.g., newspapers and blogs) are sold via intermediaries (e.g., Google), that have large market power and reportedly allocate the ads in an opaque way. We study the incentives of an intermediary to disclose consumer information to advertisers when auctioning ad impressions. We show that disclosing information that enables advertisers to optimize the allocation of ads on multi-homing consumers is profitable to the intermediary only if advertising markets are sufficiently thick. In turn, we study how disclosure affects the incentives of publishers to outsource the sale of their ads to an intermediary, and relate these incentives to the extent of consumer multi-homing, the competitiveness of advertising markets and the ability of platforms to profile consumers. We show that, even when most consumers multi-home, the publishers may be worse off by outsourcing to the intermediary, in particular if they operate in thin advertising markets. Finally, we study how the intermediary responds to policies designed to enhance transparency or consumer privacy, and the implications of these policies for the online advertising market.
Keywords: D43; D62; L82; M37; 330; online advertising; intermediary; multi-homing; privacy; transparency